Hello, can you hear me? Impact of speakerphones on phone survey responses - Alvi, Muzna; Barooah, Prapti; Gupta, Shweta; Meinzen-Dick, Ruth S.; Ringler, Claudia (International Food Policy Research Institute, 2022)
Ensuring privacy of respondents in phone surveys is especially challenging compared to face-to-face interviews. While the use of phone surveys has become more common in development research, there is little information on how the conduct of phone surveys affects responses. Using phone survey data from India and Nepal, we test the impact of speakerphone use on bias in responses by women and men. We find that 65% of women respondents in India, and 61% of women and 59% of men respondents in Nepal had their phone on speaker during the survey. Speakerphone use is lower when women are matched with the same enumerators in the second round. Speaker use was associated with lower reported agency by women over their own income and the income of their spouse, while it is opposite for men. Our findings have important implication for the collection, design, and analysis of phone survey data.